PENDAYAGUNAAN DANA WAKAF TUNAI DALAM UPAYA MENGENTASKAN KRISIS AIR BERSIH DI YAYASAN MINHAJUS SUNNAH SURABAYA - Wibowo, Wildan Rahmat; Hasanuddin, Muhammad; Aisyah, Iis Siti (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2021)
Water is the most important thing for all aspects of life. Today, many water problems arise as a result of the decreasing amount of clean water. This is the obligation of the Central and Regional Governments to provide clean water services to the community. However, considering the wide coverage area of Indonesia and the limited government funds, it requires the support of the private sector to overcome these problems. One of them is Islamic philanthropy, especially waqf management. This study aims to determine the mechanism for utilizing cash waqf funds and the factors supporting and inhibiting the utilization of waqf funds in the clean water supply program at the Minhajus Sunnah Foundation Surabaya. This research uses a descriptive qualitative method, namely by describing the actual information that occurs in the field (field research). Data was collected by doing interview, observation, and documentation. The result of this research is the mechanism for utilizing waqf funds at the Minhajus Sunnah Surabaya Foundation, the cash waqf funds themselves obtained from their permanent donors (wakif), namely the Dar Al Ber Society Foundation which is based in Dubai, United Arab Emirates. The fund that is given according to the wishes of the Dar Al Ber Society Foundation with the terms and specifications of the project that had been determined by them. This form of utilization of waqf funds is a form of distribution by providing services directly to the community in the form of building wells.Keywords: waqf, cash waqf, utilization of waqf, water crisis